Factors affecting turnover intention of Nigerian employees: the moderation effect of organizational commitment - Abet, Zanak; Mohd Anuar, Mohd Ashraff; Arshad, Mohd Mursyid; Ismail, Ismi Arif (Elsevier, 2024)
Purpose: Examining turnover as a noteworthy concern for businesses irrespective of their scale, this research delves into the factors influencing the inclination of employees in small and medium-sized enterprises to depart from their current workplaces. Additionally, the study explores how organizational commitment moderates the connections between attitude, subjective norms, perceived behavioral control, and intentions to leave. Methodology: Six hypotheses were formulated regarding the links between the components of the initial Theory of Planned Behavior and organizational commitment. Results: The outcomes from the partial least squares structural equation modeling indicated that the three primary predictors of the Theory of Planned Behavior have a substantial impact on turnover intention, with perceived behavioral control exerting the strongest influence. Additionally, the findings highlighted that the relationship between the Theory of Planned Behavior constructs and turnover intention is moderated by organizational commitment. Practical Implications and Originality: In this research, an expanded rendition of the Theory of Planned Behavior was employed to bring novel insights into the realm of organizational commitment among workers in small and medium-sized enterprises. © 2023 The Authors